Data structures and algorithms in Java - Goodrich, Michael T.; Roberto Tamassia (New York : John Wiley & Son, Inc., 2001)
Using the power of technology to go beyond the borders of the printed page, Goodrich and Tamassia have created a book that is conceptually elegant and innovative. It incorporates the object-oriented design paradigm, using Java as the implementation language while also providing the fundamental intuition and analysis of each data structure studied.
1. Java programming -- 2. Object-oriented design -- 3. Analysis Tools -- 4. Stacks, queues, and deques -- 5. Vectors, lists, and sequences -- 6. Trees -- 7. Priority queues -- 8. Dictionaries -- 9. Search trees -- 10. Sorting, sets, and selection -- 11. Text processing -- 12. Graph -- A. Useful mathematical facts -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)